The GacA-GacS Type Two-Component System Modulates the Pathogenicity of Dickeya oryzae EC1 Mainly by Regulating the Production of Zeamines - Chen, Yufan; Li, Yanchang; Zhu, Minya; Lv, Mingfa; Liu, Zhiqing; Chen, Zhongqiao; Huang, Ying; Gu, Weihan; Liang, Zhibin; Chang, Changqing; Zhou, Jianuan; Zhang, Lian-Hui; et al. (Molecular plant-microbe interactions, 2022)
The GacS-GacA type two-component system (TCS) positively regulates pathogenicity-related phenotypes in many plant pathogens. In addition, Dickeya oryzae EC1, the causative agent of soft rot disease, produces antibiotic‐like toxins called zeamines as one of the major virulence factors that inhibit the germination of rice seeds. The present study identified a GacS-GacA type TCS, named TzpS-TzpA, that positively controls the virulence of EC1, mainly by regulating production of the toxin zeamines. RNA-seq analysis of strain EC1 and its tzpA mutant showed that the TCS regulated a wide range of virulence genes, especially those encoding zeamines. Protein-protein interaction was detected between TzpS and TzpA through the bacterial two-hybrid system and pull-down assay. In trans expression of tzpA failed to rescue the defective phenotypes in both the ΔtzpS and ΔtzpSΔtzpA mutants. Furthermore, TzpA controls target gene expression by direct binding to DNA promoters that contain a Gac-box motif, including a regulatory RNA rsmB and the vfm quorum-sensing system regulator vfmE. These findings therefore suggested that the EC1 TzpS-TzpA TCS system mediates the pathogenicity of Dickeya oryzae EC1 mainly by regulating the production of zeamines. [Formula: see text] Copyright © 2022 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license .